Echocardiography of transposition of the great arteries*. (18th January 2013) - Mahle, William T.; Gonzalez, Javier H.; Kreeger, Joseph; Marx, Gerald; Duldani, Gul; Silverman, Norman H.
Abstract: The successful diagnosis, surgical planning, and long-term care of children with transposition of the great arteries require high-quality cardiac imaging with echocardiography. Echocardiography must identify the relevant anatomic variants of transposition of the great arteries, such as of ventricular septal defects and aortic arch anomalies. Methodical and detailed imaging of the coronary arteries is particularly important, as translocation of the coronary arteries is a critical component of the arterial switch procedure. Familiarity with the potential coronary artery variants and the ideal imaging planes is essential for an echocardiographer. Knowledge of both the early and late complications following the arterial switch procedure is essential to optimise post-operative echocardiography. These complications can include residual lesions leading to haemodynamic compromise or progressive late phenomena, such as aortic root dilatation and aortic insufficiency. Echocardiography will continue to be the cornerstone to the lifelong management of transposition of the great arteries, and improvements in technology and increased familiarity with modalities such as stress echocardiography will enhance the role of advanced imaging even further.